2020
DOI: 10.9734/arrb/2020/v35i430213
|View full text |Cite
|
Sign up to set email alerts
|

Histological Response of Clarias gariepinus to Varying Concentrations of Pharmaceutical Effluents

Abstract: For the past few decades, environmental pollution is considered a major global problem for public health and this problem has continued to impact aquatic environment. Pharmaceutical discharges are major sources of pollution that poses serious threat to aquatic animals like fish, therefore, this work aimed at evaluating the histological architecture of the gill tissues of Clarias gariepinus on exposed to sub-lethal concentrations of pharmaceutical effluents using standard laboratory procedure. The physicochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The fish exposed to pharmaceutical effluent also exhibited pathological injuries on gills, liver, and kidneys. Akinpelu et al, 46 found histological alterations like infiltration of secondary lamellae, oedema, congestion of the blood vessels, epithelial thickening and lifting, and necrosis in the gill tissues of Clarias gariepinus upon exposure to sublethal concentrations of pharmaceutical effluents in dose-dependent manner. Dos Santos et al, 47 found neurotoxic and respiratory effects in a Neotropical fish species, Phalloceros harpagos exposed to two common human used drugs namely paracetamol (analgesic and antipyretic) and propranolol.…”
Section: Impacts Of Residual Pharmaceuticals On Thementioning
confidence: 99%
“…The fish exposed to pharmaceutical effluent also exhibited pathological injuries on gills, liver, and kidneys. Akinpelu et al, 46 found histological alterations like infiltration of secondary lamellae, oedema, congestion of the blood vessels, epithelial thickening and lifting, and necrosis in the gill tissues of Clarias gariepinus upon exposure to sublethal concentrations of pharmaceutical effluents in dose-dependent manner. Dos Santos et al, 47 found neurotoxic and respiratory effects in a Neotropical fish species, Phalloceros harpagos exposed to two common human used drugs namely paracetamol (analgesic and antipyretic) and propranolol.…”
Section: Impacts Of Residual Pharmaceuticals On Thementioning
confidence: 99%